PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN KAS TERHADAP PROFITABILITAS PADA PT.SOXAL BATAMINDO INDUSTRIAL GASES - Windyana, Windyana; Yando, Agus Defri (SCIENTIA JOURNAL, 2020)
The purpose of this paper is to determine the development of account recevable, cash turnover, and profitability in the public company Soxal Batamindo Industrial Gases. To determine the effect of cash turnover and accounts receivable turnover on profitability partially and simultaneously on pt.soxal. Secondary data used in this study is PT.Soxal Company's Financial Statements from 2015-2019. The analytical method used is to do calculations on variables, descriptive tests, classic assumption tests, multiple linear regression, t tests and f tests. Based.on research results partially cash turn over has a probability abaout 0.938 which means there is no influence between cash turnover and probability. Partyally, receivable turnover has a positivy but no significant effect on probability (ROA). The company is expeted to increase working capital every year, because of the increase of working capital than the activity of the company will run smoothly and generate maximum profit.